Higher Education and Employability - Calilova, Fatma; Alasgarova, Chinara; Abilzada, Gunay (ADA University, 2021)
The relationship between higher education and employability has been transformed into a growing pressure on both undergraduate students and higher education institutions. This research paper focuses on defining the employability challenges which can be recognized by future bachelor's degree graduates, universities and employers from the perspective of the HEIs. The target population of this research was 210 fresh-out bachelor students of three "innovative" Azerbaijani Universities. To answer the research questions among the sample population, the survey was used as a research instrument. The findings obtained from the research allowed to claim that most of the undergraduate students' workplaces are either partly related or not related to their qualifications, which proves not only the mismatch between the skills taught at universities and the needed employability skills, but also the lack of vacancies for bachelor's degree graduates as a result of stiff competition in labor market in Azerbaijan. Thus, we recommend strengthening the role of HEIs on the result of employability, and creating a safe environment where students can learn the required skills and knowledge.
Keywords: Education; Undergraduate employability; Bachelor's degree students; Higher education; Employability skills; Employment decisions